Levantamento nutricional de bananais do Vale do Ribeira-SP pela análise foliar - Godoy, Leandro José Grava de [UNESP]; Gomes, Juliana Macedo [UNESP]; Mendonça, José Carlos de (Universidade Federal do Paraná, 2013)
The region of the “Vale do Ribeira, SP” is responsible for 70% of banana production in the state of São Paulo. The cultivation of bananas plants requires large amounts of nutrients for proper development. The survey of the leaf nutrient concentration of crops aims to identify the nutrients deficiencies and excesses, and to direct regional fertilization researches to be planned. The objective of the work was to survey the nutritional status of banana crop in “Vale do Ribeira, SP”. We used results of nutrientleaf analysis of and “Prata” and “Cavendish” subgroups cultivars of samples collected in banana crops representatives in “Vale do Ribeira”, in the period 1998 to 2005. The leaf samples were collected in banana crops of the following counties: Cajati, Eldorado, Jacupiranga, Pariquera-Acu, Registro and Sete Barras. Were determined the leaf concentration of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn. Most banana crops sampled showed deficiency of N and S. The deficiency of K observed in some banana crops must be due to the imbalance cation (K: Mg: Ca). The B was found in the nutrient excess more frequently. The average leaf content of K, Ca, S, Cu and Zn was higher in “Prata” subgroup than in the “Cavendish” subgroup.

A região do Vale do Ribeira é responsável por 70 % da produção de banana do Estado de São Paulo. O cultivo da bananeira requer grandes quantidades balanceadas de nutrientes para um desenvolvimento adequado. O levantamento dos teores foliares de nutrientes das culturas tem a finalidade de identificar a existência de deficiências e excessos de nutrientes, e direcionar as pesquisas regionais de adubação a serem planejadas. Objetivou-se com o trabalho realizar o levantamento do estado nutricional de bananais do Vale do Ribeira, SP, a partir da análise química foliar dos subgrupos Cavendish e Prata. As amostras foram coletadas em talhões representativos, no período de 1998 a 2005, nos municípios de Cajati, Eldorado, Jacupiranga, Pariquera-Açu, Registro e Sete Barras. Determinou-se os teores de N, P, K, Ca, Mg, S, B, Cu, Fe, Mn e Zn. A maioria dos bananais amostrados apresentou deficiência de N e S. A deficiência de K observada em alguns bananais deve ser devido ao desequilíbrio catiônico (K:Mg:Ca). O B foi o nutriente encontrado em excesso com maior freqüência. A média do teor foliar de K, Ca, S, Cu e Zn foi maior no subgrupo Cavendish.
Nutritional survey of banana crops of the “Vale do Ribeira-SP” by the foliar analysis
Keywords: Banana; Foliar analysis; Musa sp.; Banana; Análise química foliar; Musa sp.